2020
DOI: 10.1136/bmjsem-2020-000761
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief lifestyle intervention targeting mental health staff: analysis of physical fitness and activity in the Keeping Our Staff in Mind study

Abstract: BackgroundPeople with mental illness die on average 15 years less than the general population, primarily to cardiometabolic disease. Lifestyle interventions are effective in reducing cardiometabolic risk but are not routinely provided to mental health consumers. Lifestyle interventions targeting mental health staff may be beneficial in changing culture surrounding physical health and subsequently improving consumer outcomes. This study examines exercise and fitness outcomes of a targeted lifestyle intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Participants felt that they had experienced positive changes in their knowledge, attitudes, and behaviours to their own physical health. This aligns with quantitative results from the KoSiM program that demonstrated significant improvements to dietary and exercise patterns and consequently a reduction in waist circumference of mental health staff that participated 21,31,32 . This study also found changes in attitude beyond just the individual participant and their own physical health.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Participants felt that they had experienced positive changes in their knowledge, attitudes, and behaviours to their own physical health. This aligns with quantitative results from the KoSiM program that demonstrated significant improvements to dietary and exercise patterns and consequently a reduction in waist circumference of mental health staff that participated 21,31,32 . This study also found changes in attitude beyond just the individual participant and their own physical health.…”
Section: Discussionsupporting
confidence: 85%
“…This aligns with quantitative results from the KoSiM program that demonstrated significant improvements to dietary and exercise patterns and consequently a reduction in waist circumference of mental health staff that participated. 21,31,32 This study also found changes in attitude beyond just the individual participant and their own physical health. Participants were more focused on the physical health of their immediate families, their work colleagues, and people experiencing SMI with whom they work.…”
Section: Discussionsupporting
confidence: 57%
“…28,29 Three of the articles were associated with the Global Corporate Challenge® [30][31][32] and three evaluated separate waves of the Keeping our Staff in Mind project. [33][34][35] A decision was made to extract and analyzed data from each article separately and therefore the use of the word article rather than study is used throughout this review. Table 3 summarizes the findings of the following characteristics; geographical location, chronic disease risk factors targeted, study designs and methodology, industry/workplace setting, intervention length and follow up evaluation…”
Section: Resultsmentioning
confidence: 99%
“…The provision of exercise facilities may additionally be effective in improving staff attitudes towards physical activity and may increase staff confidence in motivating physical activity amongst patient groups (Bartels et al, 2015). This may, in turn, have an indirect impact on patient engagement in similar interventions (Fibbins et al, 2020), which is important as people living with mental health conditions have substantially poorer physical health than the general population and increased premature mortality, which may be reversed and/ or managed through exercise (Correll et al, 2017;John et al, 2018).…”
Section: Exercise Provision For Mental Health Staffmentioning
confidence: 99%
“…Recently, the Keeping our Staff in Mind (KoSIM) study set out to see whether individualized physical activity and nutritional counselling for mental health staff yields positive health impacts (Fibbins et al, 2020; Rosenbaum et al, 2020). The results highlighted large increases in staff confidence in screening, promoting, and actively intervening to improve physical health outcomes of patients and positive attitudes towards metabolic monitoring of patient groups they care for, alongside improvements in staff cardiometabolic markers (Fibbins et al, 2020; Rosenbaum et al, 2020). Further, focus groups with mental health staff and patients investigating perspectives on implementing exercise interventions for psychiatric inpatients identified positive attitudes towards the provision of exercise facilities for staff groups as well as patients.…”
Section: Introductionmentioning
confidence: 99%